Chemical Composition and Meat Quality Attributes of Indigenous Sheep and Goats from Traditional Production System in Tanzania - Dismas S. Shija; Louis A. Mtenga; Abiliza E. Kimambo; Germana H. Laswai; Daniel E. Mushi; Dynes M. Mgheni; Angello J. Mwilawa; Eligy J. M. Shirima; John G. Safari (Asian-Australasian Journal of Animal Sciences, 2013)
The aim of the study was to compare chemical composition and quality attributes of meat between male long fat tailed sheep (n = 17) and Small East African goats (n = 17) existing in Tanzania. Animals of 1.5 to 2 yrs in age and live body weight of 22.59±0.50 kg were purchased from livestock auction markets. Animals were fasted for 18 h and slaughtered according to standard halal procedure. Left carcasses were dissected into muscles, fat and bone and the muscle and fat were mixed together and chemically analysed. Meat quality attributes were measured based on Muscle longissimus thoracis et lumborum excised from right sides of carcasses. Goat carcasses had significant higher (p = 0.0302) moisture content (70.65% vs 66.96%) and lower (p = 0.0027) ether extract (2.49% vs 5.82%) than sheep but there was no significant species differences in protein and ash content. Sheep had lower (p = 0.0157) ultimate pH (5.74 vs 5.88) and higher (p = 0.0307) temperature (3.77°C vs 3.15°C) than goat carcasses. Sheep meat had lower (p = 0.0021) shear force values (29.83 N vs 34.07 N) than goat. Within species, at day 9 of ageing, meat tenderness improved (p = 0.0001) by 44.63% and 34.18% for sheep and goat. Pooled data showed that at d 9 of ageing, meat tenderness improved (p = 0.0001) by 39.25% (from 39.54 N to 24.02 N) compared to tenderness of meat which was not aged at day one of slaughter. The present study demonstrated the differences in chemical composition and quality attributes of meat existing between sheep and goats originated from East Africa.